User-Friendly Evaluation of Three-Dimensional Visualization of Atomic Models on Mobile Teaching Module Application: PyLo-AR - Ramadhan, Imam; Hasyim, Mutahharah; Nurlina, Nurlina (Jurnal Pendidikan Fisika Indonesia, 2024)
Integrating augmented reality technology in physics education provides students with a novel learning experience, requiring proficient skills and effective organization. PyLo-AR, a Marker-Based Augmented Reality (M-AR) mobile app, teaches atomic models (Dalton, Thomson, Rutherford, Bohr). This study assesses PyLo-AR's user-friendliness using SUS and UEQ methods, involving highschool students. SUS scores indicate a satisfactory usability level (71). UEQ averages are 1.797 (Attractiveness), 1.700 (Perspicuity), 1.577 (Efficiency), 1.605 (Dependability), 1.941 (Stimulation), and 1.067 (Novelty). The category of the stimulation indicator is excellent, which means the PyLo-AR application is highly engaging for learners. The attractiveness, efficiency, and accuracy indicators are rated as "good," indicating that the PyLo-AR application is enjoyable and reliable in understanding the characteristics of each atom model through its 3D visualization features. Meanwhile, the clarity and novelty indicator categories are rated as "above average," suggesting that the PyLo-AR application is sufficiently efficient and easy to understand with an organized User Interface (UI). Thus, the PyLo-AR application has met the criteria for being a user-friendly application for learners to comprehend the characteristics of each atom model.